The treatment of preaching in the "Historia del famoso predicador Fray Gerundio de Campazas": Explicit rhetoric and implicit rhetoric - Celma, María Pilar (Tropelías: Review of Literary Theory and Comparative Literature, 2019)
Traditional readings of HFGC emphasize the parodical nature of the work. However, in order to evaluate the effectiveness of P. Isla’s proposals against the excesses in preaching, is neccesary to analyze the actual circumstances of the moment, paying close attention to 1.- the causes of the satirazed preaching practices, 2.- the answers offered up to that point, and, 3.- P. Isla personal stance, as manifested in a short and almost forgotten work written years before HFGC. Islas’s aim is not parody in itself but to contribute, in the form of practical measures, to the debate that s in progress. And so Islas’s analysis of the "modus concionandi" encompasses three different aspects: a diagnosis of the situation; a strong criticism of many of the model works circulating those years; and a theoretical discussion -through relevant characters in the novel- about what preaching should be. A very complex task that renders HFGC a subtle novel, whose implied rethoric we try to make explicit.